Menggali Potensi Vegetasi Adaptif Dan Benilai Ekonomi Pasca Erupsi Gunung Marapi Di Nagari Canduang Koto Laweh Kabupaten Agam - Alexander Syam; Tiara Suci Ramadani; Nila Sari (Kilau Publishing, 2025)
On December 3, 2023, at 2:54 PM WIB, an explosive eruption occurred with an eruption column height of approximately 3,000 meters above the summit (5,891 meters above sea level) and recorded on a seismograph with a maximum amplitude of 30 mm and a duration of 4 minutes 41 seconds. The eruption column was observed to be gray with thick intensity leaning towards the east. The eruption was also accompanied by pyroclastic flows to the north with a sliding distance of 3 km from the summit. A number of commodity fields such as rice, sugar cane, and other crops were recorded to be covered in volcanic ash.